Fabricating Piezoelectric Tape of PZT-SKN. (September 2019) - Hemadhulin, O.; Kongphimai, J.; Photankham, W.; Srinuanlae, P.; Wattanasarn, H.
Abstract: Tape ceramics are widely used in the sensor and electronic industries. In this work, we studied the ferroelectric properties of the 0.975Pb(Zr0.52 Ti0.48 )O3 -0.025Sr(K0.25 Nb0.75 )O3 tape ceramic; (PZT-SKN). We fabricated the PZT-SKN using doctor blade technique with the slurry, obtained from the calcined of PZT-SKN mixing with organic solution. The crystalline structure was investigated by using X-ray diffraction, relative density, and Vickers Hardness technique. We also determined the dielectric properties and polarization electric field loops. The results of crystalline structure show that the percentage of perovskite is 97.57 %, the relative density is 98.4 %, and Vickers Hardness is 107 MPa. At the thickness 0.89 mm, the dielectric constant temperature is 1499 at 532 °C, the remnant polarization is 17 μC cm −2, Currie temperature is 552 °C, and piezoelectric coefficient is 235 pC N −1 . The PZT-SKN tape ceramic has the ferroelectric properties better than tablet ceramic.